L’échec de la quête de la liberté chez une mère et sa fille : Gervaise et Nana dans Les Rougon-Macquart - Marzel, Shoshana-Rose (Romanica Silesiana, 2025)
This article examines the failure of the pursuit of freedom in Les Rougon-Macquart through the parallel destinies of Gervaise and her daughter Nana. It first analyzes how each woman initially succeeds, albeit briefly, in achieving a form of autonomy: Gervaise through hard work and moral integrity, Nana through transgression and seduction. The second part of the article focuses on the subsequent loss of that freedom. Drawing on naturalist principles such as heredity and environment, Zola constructs a deterministic universe in which individual aspirations are ultimately crushed. Gervaise ’ s gradual degradation and Nana ’ s sudden death both reflect not only the weight of social and biological constraints, but also Zola ’ s aesthetic and ideological objectives. The article concludes by placing these fictional trajectories within the historical context of nineteenth-century women ’ s limited social roles, showing how Zola ’ s fiction exposes the tragic dead ends of female emancipation in a patriarchal society.